The PBL-STS Model for Achieving Critical Thinking Skills in Elementary School Students - Setiawan, Fajar; Masitoh, Siti; Mariono, Andi (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
The research was motivated by the low learning outcomes of students, where as many as 57% of thirty students still needed to achieve the minimum completeness criteria (KKM). Moreover, in practice, the assessment of learning outcomes developed by teachers needs to be oriented toward measuring critical thinking skills. This study aims to describe the effectiveness of the Problem-based Learning (PBL) model with the integrated pattern of Science, Technology, and Society (STS) education in fourth-grade elementary school students. In this study, Borg and Gall's development research model was used, a process carried out to produce and test an educational product. The results showed (1) Each statement, both positive and negative statements, obtained an average percentage of 85.4% and was declared good; and (2) the average pretest score was only 32.7 and increased after the PBL-STS model was applied with a posttest score of 83.3. The average n-gain value obtained is 0.75 and is included in the high category. In addition, the significance value (2-tailed) is 0.00 <0.05, so the application of the PBL-STS model has a significant effect on the achievement of learning objectives (students' critical thinking skills learning outcomes), or is accepted.